An Exploration of the Cellular Microenvironment of the Female Pig Urethra: Translational Insights for Urological Research - Agustín Cartes; Caroll Stoore; María Soledad Baquedano; Christian Hidalgo; Felipe Lillo; Eduardo Landerer; Galia Ramírez-Toloza; Rodolfo Paredes (Biology)
Urinary incontinence is a widespread issue, particularly among women, with effective treatments remaining elusive. The pig, and especially the female pig, stands as a promising animal model for the study of this condition, due to its anatomical similarities to humans. The aim of this study was to explore the largely uncharted muscular structure of the female pig urethra, linking urethral muscle dysfunction to incontinence. We examined histological sections from the urethras of six sows using Hematoxylin-Eosin and Masson’s trichrome staining for morphometric analysis. The statistical significance of cellular disposition was determined through analysis of variance (ANOVA), followed by a Tukey post hoc test to elucidate specific inter-group differences. Our analysis revealed segment-specific epithelial differences, including variations in cell layers, sparse acinar glands, rich vasculature, and distinct muscle fibers with diverse regional distributions. Notably, significant differences in muscular area and tissue distribution were identified between the proximal, middle, and distal segments of the urethra (p < 0.001). The observed anatomical variations, along with the cellular similarities between pigs and humans, establish the female pig as a crucial translational model for advancing urological research. Specifically, these findings provide a foundation for the development of innovative therapeutic strategies and surgical techniques that can be directly applied to improve outcomes in human urological conditions.